2008
DOI: 10.1111/j.1525-1594.2008.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐aortic Balloon Pump‐induced Pulsatile Flow Reduces Coagulative and Fibrinolytic Response to Cardiopulmonary Bypass

Abstract: The aim of this study is to evaluate if a simple intra-aortic balloon pump (IABP)-induced pulsatile perfusion reduces activation of coagulative system during cardiopulmonary bypass (CPB). Ninety-six patients undergoing preoperative IABP were randomized to nonpulsatile CPB with IABP discontinued during cardioplegic arrest (Group A) or IABP-induced pulsatile CPB (Group B). White blood cells (WBC), hematocrit (Ht), platelets (PLTs), International Normalized Ratio (INR), fibrinogen, activated partial thromboplasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 22 publications
0
30
0
1
Order By: Relevance
“…Recent studies have focused not only on the beneficial effects of preoperative IABP deployment in high-risk patients undergoing coronary artery bypass grafting operations [8,9] but also on the continuation of IABPinduced pulsatile perfusion during CPB and cardioplegic arrest [10][11][12] because it contributes to better renal, hepatic, and pancreatic preservation [10], more favorable regional and global perfusion during CPB and throughout the early postoperative period [11], reduced coagulative and fibrinolytic response to CPB [12], and improved lung function in patients with obstructive pulmonary disease [13]. In contrast to these results, Voss and colleagues [2] recently concluded that efforts to obtain pulsatility were not justified because capillary leak and hemolysis was higher than during nonpulsatile CPB perfusion.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have focused not only on the beneficial effects of preoperative IABP deployment in high-risk patients undergoing coronary artery bypass grafting operations [8,9] but also on the continuation of IABPinduced pulsatile perfusion during CPB and cardioplegic arrest [10][11][12] because it contributes to better renal, hepatic, and pancreatic preservation [10], more favorable regional and global perfusion during CPB and throughout the early postoperative period [11], reduced coagulative and fibrinolytic response to CPB [12], and improved lung function in patients with obstructive pulmonary disease [13]. In contrast to these results, Voss and colleagues [2] recently concluded that efforts to obtain pulsatility were not justified because capillary leak and hemolysis was higher than during nonpulsatile CPB perfusion.…”
Section: Commentmentioning
confidence: 99%
“…Our animal model resembles IABP application as previously used in clinical and experimental studies with and without CPB [10][11][12][21][22][23]. An IABP balloon of 25 mL was chosen to ensure conditions as previously described [21][22][23].…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…CPB and surgical techniques were standardized and did not change during the study period. All patients received linear CPB [11][12][13]. In all patients, CABG was performed through a median sternotomy.…”
Section: Anesthesiamentioning
confidence: 99%
“…The recent literature has reported a beneficial impact of OPCABG on endothelial activation and SIRS [3,4]. Moreover, although non-pulsatile blood flow obtained with standard CPB circuits is considered an acceptable, non-physiologic compromise conferring few disadvantages (including lack of induction of the inflammatory response) [1,4], we have reported beneficial effects on splanchnic, renal, respiratory and haemostatic functions when intra-aortic balloon pump (IABP)-induced pulsatile perfusion has been employed in routine coronary surgery [5,6]. The relative effects of all of these options on endothelial activation, inflammatory responses and clinical outcomes are unknown, however.…”
Section: Introductionmentioning
confidence: 95%